2 Epilepsy in people with an intellectual disability- managing the neuropsychiatric challenges!. (28th May 2019) - Kerr, Mike
Abstract : Professor Mike Kerr studied medicine in Bristol (UK), General Practice in York and Psychiatry in Cardiff. His clinical practice is in the epilepsies associated with intellectual disability and in the assessment and treatment of epilepsy and psychiatric disorder. He has been closely associated with initiatives in improving the public health of people with an intellectual disability including developing the Cardiff Health Check, which is used across England and Wales. Academically he has published widely on healthcare, epilepsy and intellectual disability and held research grants from many funding bodies. He is vice chairperson of SUDEP ACTION. He is chair of the International League Against Epilepsy (ILAE) commission on psychiatric aspects of epilepsy. He has been appointed as an Ambassador for Epilepsy by the ILAE and International Bureau for Epilepsy. There is a close relationship between epilepsy and people with intellectual disability, with an estimated 22% prevalence of epilepsy. The epilepsy is also known to be more severe with an increase in likelihood of chronicity and early mortality. From a neurological point of view the group presents challenges in diagnosis, investigation and treatment choice. Especially as so many individuals have childhood severe epilepsies, with seizure freedom a challenging goal. A specific management issue is that the population presents a range of neuropsychiatric challenges in terms of diagnosis, behavioral co-morbidity, and the presence of psychiatric comorbidity. These conditions significantly hinder the ability to manage patients and intensify the impact of epilepsy on the individuals and carers. To some degree this would appear no different to the challenges posed within the epilepsy population without intellectual disability. However, issues of communication need, varied aetiology of the intellectual disability and care provision intensify the complexity of neuropsychiatric presentation. In the era of personalized and precision medicine people with an intellectual disability are now at the forefront of medical practice. With individual aetiology, in particular, driving assessment and intervention. This paradigm can be applied to neuropsychiatric disorders in people with an intellectual disability, expanding our knowledge of the conditions and improving our clinical formulations and interventions. In this presentation I will discuss the nature of neuropsychiatric presentations in people with an intellectual disability, its aetiology and how clinicians may manage these conditions within the setting of epilepsy care.